Communication and Health on South America. Cases: Bolivia, Chile, Colombia - Carlos Andrés Martínez Bele\~no (Journal of Education, Psychology and Social Sciences, 2014)
Nowadays, communication and health have established a space in the Latin American public agenda after the loss of force of the health education strategy when confronted by more dialogic processes in conceptual and practical terms, in which the use of media and empowerment of vulnerable populations have to be encouraged in the solution to their problems. In that sense from a multiple case study and a type of qualitative descriptive research using an explanatory scope, this work aims to mention the reach of communication in the promotion of health plans in countries such as Bolivia, Chile and Colombia. Likewise, the data analysis was structured having into account variables such as cognition, self-sufficiency, motivation, molding, affect, behavior which are some characteristics of the theories of health communication. Overall, it was possible to understand that communication and health as articulated processes, accompany, facilitate and promote human development and it is necessary that each country, city or community that seeks to develop a political and social project, should orientate their actions toward the most vulnerable population; where economic, social and environmental responds to their needs and their social context. Finally, Communication for Development recognizes that the protection of social, economic and environmental capital is essential for productive development, and that the individual should play a key role in deciding on their own development and that of their environment. Hence health communication as a favorable response and alternative
Keywords: 330; Communication; Development; Health; Health Promotion; Health Communication